The Effects of Artificial Lake Space on Satisfaction and Restorativeness of the Overall Environment and Soundscape in Urban Parks - Qi, Ying; Fang, Xingyue; Gao, Tian; Qiu, Ling (Frontiers in Built Environment, 2021)
Abstract: Several studies proved that soundscape in blue space is conducive to human health and well-being, but few explore which blue space characteristics would contribute to better soundscape and visiting experience. Therefore, an on-site questionnaire investigation was conducted in two artificial lakes in Xi’an, China. The eight Perceived Sensory Dimensions (PSDs) as a landscape assessment tool were applied to identify the characteristics of artificial lake space in urban parks. The results showed that (1) In artificial lake space, overall environment and soundscape were reached a very satisfactory level in general, while the respondents’ perceived the level of overall restorativeness and soundscape restorativeness were just medium, which indicated that the quality of artificial lake space needs to be improved. (2) The artificial lake space had the most obvious characteristics of prospect, social and space by people’s perceptions; serene and nature were in the medium; refuge, rich in species and culture were the least. (3) The eight PSDs of artificial lake space, except for social, were positively correlated with soundscape satisfaction, overall satisfaction, soundscape restorativeness and overall restorativeness. Moreover, among them, serene was the most significant characteristic in artificial lake space. These findings could be instructive to design of urban park with artificial lakes for improving users’ visiting satisfaction and restorativeness.